Prevalensi Dan Karakteristik Penderita Katarak Senilis Di Desa Mendalanwangi, Sidorahayu, Dan Cepokomulyo Di Kabupaten Malang Jawa Timur - Handayani, Nina; Dyatmiko, Hendrian; Prayitnaningsih, Seskoati; Andarini, Sri (Journals of Ners Community, 2023)
To study the prevalence and characteristics of age related cataract in an adult population in Malang East Java. A population based, cross sectional study of 692 adults (aged > 50 years) were selected from September until December 2019 from Smarthealth Database. The presence of lens opacity was examined by slit lamp biomicroscopy and evaluated according to Lens Opacity Classification System III. The subtype of cataract present, including nuclear, cortical, and posterior subcapsular, were identified from univariate and 95% confidence interval (CI) for association of each specific type of cataract with age, health examination and medical history. A total of 692 patients with aged > 50 years old were included in this study. The prevalence of cataract was 48,7% in participants over 50 years old. From 337 respondents were in the age range 50-70 years, as many as 240 people (71,22%) patients were female, as many as 206 people (61,13%) patients with primary school education, and 151 people (44,8%) patients work as housewife. The standardized prevalences of clinically significant nuclear, cortical, and posterior subcapsular cataract (PSC) were 7,42%, 7.72%, and 5.34% in an adult population in Mendalanwangi, Sidorahayu and Cepokomulyo village in Malang districs. The prevalence of nuclear, cortical and posterior subcapsular cataract increased high prevalence of age related cataract in the adult population remains a severe public health problem.